Achieving oral and planetary health; how sports dental medicine can pioneer and realize transformation in oral healthcare - Avgerinos, Stavros; Fisher, Julian; Krejci, Ivo; Saiyed, Aafreen; Banerjee, Avijit (Frontiers in Oral Health, 2025)
The present manuscript is consistent with the objectives and scope of Frontiers in Oral Medicine, particularly the Oral Health Promotion section. The text presents a forward-looking perspective on how the potential of sports dental medicine can act as a catalyst for promoting sustainable and AI-enhanced oral healthcare. The article discusses a conceptual shift toward preventive, interprofessional and transdisciplinary collaboration, technology-integrated models of care, including key themes such as health promotion, system-level innovation and planetary health.